Analysis of Risk Factors for Dengue Hemorrhagic Fever in Riau Province using Negative Binomial Regression - Rangkuti, Aisyah Azhari; Sirait, Haposan (Indonesian Operations Research Association (IORA), 2023)
Dengue Hemorrhagic Fever (DHF) is a serious threat in Riau province, Indonesia. To better understand and control the spread of dengue fever, this research aims to analyze the factors that cause dengue fever. This study aims to identify significant risk factors that influence the spread of dengue fever in Riau Province. The Negative Binomial Regression Method was used to identify factors associated with the increase in dengue fever cases in Riau. The variables evaluated include population density of the Aedes aegypti vector , level of environmental cleanliness, prevention practices, and socio-economic factors. In addition, the best model was selected to overcome overdispersion in the data. The results of the analysis show that factors such as population density of the Aedes aegypti vector , environmental cleanliness, and the level of public understanding about dengue prevention practices have a significant influence on the spread of dengue fever in Riau. The best model used to overcome overdispersion in the 2021 dengue fever case data in Riau is Negative Binomial Regression. This research provides a deeper understanding of the factors causing dengue fever in Riau and selects an appropriate statistical model for analyzing data that experiences overdispersion. Negative Binomial Regression proved to be more appropriate in overcoming the problem of overdispersion in the data. These results can be used as a basis for designing more effective dengue prevention and control strategies and provide guidance for more targeted interventions in fighting dengue fever in this region.